2014
DOI: 10.1371/journal.pone.0085142
|View full text |Cite
|
Sign up to set email alerts
|

DL-β-Aminobutyric Acid-Induced Resistance in Soybean against Aphis glycines Matsumura (Hemiptera: Aphididae)

Abstract: Priming can improve plant innate capability to deal with the stresses caused by both biotic and abiotic factors. In this study, the effect of DL-β-amino-n-butyric acid (BABA) against Aphis glycines Matsumura, the soybean aphid (SA) was evaluated. We found that 25 mM BABA as a root drench had minimal adverse impact on plant growth and also efficiently protected soybean from SA infestation. In both choice and non-choice tests, SA number was significantly decreased to a low level in soybean seedlings drenched wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 80 publications
(78 reference statements)
5
32
0
Order By: Relevance
“…Different letters indicate significant differences between curves (pairwise log-rank post hoc tests with Bonferroni correction, p < 0.05) Plymale et al 2007). The same pattern was also reported for some other inducers as cis-jasmone (Moraes et al 2008) and BABA (Zhong et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Different letters indicate significant differences between curves (pairwise log-rank post hoc tests with Bonferroni correction, p < 0.05) Plymale et al 2007). The same pattern was also reported for some other inducers as cis-jasmone (Moraes et al 2008) and BABA (Zhong et al 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, peroxidase catalyzes the last step of lignin biosynthesis, which plays an important role in the defense mechanism of plant hosts . Previous studies showed that BABA treatment stimulated lignin synthesis and PAL and POD activities in plant defense against pathogens and soybean aphid . Microbial products also enhanced lignin accumulation and activated the transcription of some related genes in Arabidopsis leaves, such as PAL , C4H , 4CL and CAD .…”
Section: Discussionmentioning
confidence: 99%
“…When the first trifoliolate fully expanded (V1 growth stage), 25 mL BABA–water solution (25 m m ) was applied until the substrate was drenched. This concentration was considered to be appropriate for priming soybean plants . For the control, 25 mL of water was applied.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations